(untitled) (Revista Argentina de Musicología, 2023)
Pauline Viardot, (Paris, 1821-1910), was a key figure in the European artistic world of the 19th century. She achieved well-deserved international renown both as an Opera and concert singer, composer and voice pedagogue, and was a catalyst for artistic, political and intellectual personalities. This article intends to highlight in the first place the multiplicity of possible lines of investigation around her figure, both as a role model of successful professionalization, as well as leadership and musical direction of a woman in the 19th century. Secondly, some unpublished works composed in the final decades of the 19th century in which aesthetic experimentation takes center stage will be analysed. These pieces propose a nuance to the “sound image” of this composer, a musical label that she herself contributed to delineate. In all cases, the importance of the study based on primary sources is highly recommended, to enable her professional profile visible, detached from the narratives of music history built around male figures.